The impact of the domestic gender gap on the gross domestic product: Sudan Case Study (1990-2021) - عــــلى جــماع الباشـــا, إبراهــــيم (Dirasat in Economics and Business, 2024)
The study aimed to measure the relationship between the gender gap and the GDP in the Sudanese economy (1990-2021). The problem was summed up in the question: Is there a statistically significant relationship between the gender gap and GDP in the Sudanese economy? . Suppose there is a negative, statistically significant relationship between gender gap and GDP in the Sudanese economy. Standard statistical method. The most important result is: The inverse link with linking the gender gap as an independent variable and the gross domestic product in Sudan as a dependent social variable. Ta'ali recommended, to address the gender gap in employment and education opportunities through the establishment of laws that exist for women on equal terms with men.